Pengembangan Kepemimpinan Guru PAI dalam Menumbuhkan Karakter Religius Siswa di SMK Miftahul Ulum - Juwita Pradina Aprillia; Faruq Abdul Dzaki Susilo; Agus Joko Purwanto (CV. Lentera Literasi Indonesia, 2026)
This study attempts to describe efforts to develop the leadership skills of Islamic Education teachers, the strategies used by Islamic Education teachers to foster religious character in students at school, the supporting and inhibiting factors encountered in fostering religious character in students in the development of Islamic Education teachers' leadership, and concrete examples of successful leadership development in shaping the religious character of students at SMK Miftahul Ulum, Jatidatar. This study uses a qualitative approach. The data collection methods include observation and interviews. The results of this study are: 1). Efforts made by PAI teachers to develop leadership skills 2). strategies used by PAI teachers to instill religious character in students 3). Supporting and inhibiting factors in the development of PAI teacher leadership at SMK Miftahul Ulum, Jatidatar 4). Examples of successful leadership training in shaping students' religious character